The Pedagogical Potential of Visual Images in Indonesian High School English Language Textbooks: A Micro-Multimodal Analysis - Kautsar Rahikummahtum; Joko Nurkamto; Suparno Suparno (STAI Hubbulwathan Duri, 2022)
Language textbooks mainly guide language learning and teaching activities. Most of the language textbooks used to comprise a range of visual texts, such as pictures, illustrations, and photos. The study adopts the Visual Grammar Theory by Kress and Leeuwen (2006) to elucidate the pedagogical functions of visual images and explore how such images can be exploited for learning tasks from a micro multimodal perspective. The data consist of 142 visual images in Indonesian senior high school EFL textbook grades ten (X) and eleven (XI). The findings pointed out that the textbook uses visual images' full potential to fulfill pedagogical aims. Many visual images or texts in language textbooks serve information and illustrations rather than as a decorative function. Visual images may assist students to engage effectively in learning tasks by emphasizing the meaning of information presented in images and text. This study suggests that learning activities should consider multimodal texts to contribute significantly. This research aims to enhance knowledge about the pedagogical function of visual images in textbooks and can be a reference for further exploration.